EKSPLORASI NILAI-NILAI KARAKTER DAN ASPEK PEMBELAJARAN IPA DALAM GERAKAN TARI TRADISIONAL TOGO POU SUKU PALUE - Regi, Benyamin; Theofanus Lering, Sturmius; Delfianti Bhae, Maria (Universitas Cokroaminoto Palopo, 2025)
This study aims to explore the character values contained in the traditional Togo Pou dance of the Palue ethnic group and to examine the potential aspects of Science Education (IPA) that can be derived from the movements of the dance. Togo Pou is a traditional dance from the Palue ethnic group in Sikka Regency, East Nusa Tenggara, which reflects the behavior patterns of the community through dance movements accompanied by gong and drum music. Each dance movement mirrors the meaning contained in the lyrics of the song, which invites the community to work together on tasks that cannot be done alone, such as building a boat. This research uses a qualitative approach with data collection techniques through interviews and documentation. The collected data is analyzed using the Miles and Huberman analysis model, which includes data collection, data reduction, data presentation, and drawing conclusions. The subjects of this research are the people of Dusun Lomite Bhako and traditional leaders who have a deep understanding of the meaning of the dance. The findings show that the Togo Pou dance contains character values such as religiosity, love for peace, social care, and friendliness and communication. The conclusion of this study is that this dance is not only a cultural heritage but also serves as a means to teach character values and Science Education, such as balance and coordination, which are beneficial in elementary school education.